2015
DOI: 10.1645/15-731.1
|View full text |Cite
|
Sign up to set email alerts
|

Acanthocephalan Cystacanths from Flatfish (Order Pleuronectiformes) in Tropical Australian Waters

Abstract: Cystacanths of 4 species of Acanthocephala are reported for the first time from various species of fish belonging to the Order Pleuronectiformes from waters of the western Gulf of Carpentaria and the central coast of Queensland, Australia: Corynosoma cetaceum Johnston and Best, 1942 (Family Polymorphidae), Serrasentis cf. sagittifer (Linton, 1889) and Rhadinorhynchus sp. (Family Rhadinorhynchidae), and Gorgorhynchoides sp. (Family Isthmosacanthidae). Approximately 32% of the 515 individual fish belonging to 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Serrasentis sagittifer and C. cetaceum were recently reported from paralichthyid fish at higher prevalences than those found in the present study. Barton & Smales (2015) investigated six species of the genus Pseudorhombus Bleeker, 1862, from Australian waters, and found cystacants of S. cf. sagittifer (prevalecne of 36.32%) in fish from the western Gulf of Carpentaria, and S. cf.…”
Section: Discussionmentioning
confidence: 99%
“…Serrasentis sagittifer and C. cetaceum were recently reported from paralichthyid fish at higher prevalences than those found in the present study. Barton & Smales (2015) investigated six species of the genus Pseudorhombus Bleeker, 1862, from Australian waters, and found cystacants of S. cf. sagittifer (prevalecne of 36.32%) in fish from the western Gulf of Carpentaria, and S. cf.…”
Section: Discussionmentioning
confidence: 99%
“…is the first Serrasentis species described from marine teleosts of the order Pleuronectiformes. Barton and Smales (2015) reported cystacanths of Serrasentis cf. sagittifer from six families belonging to the order Pleuronectiformes (i.e., Bothidae, Citharidae, Cynoglossidae, Paralichthyidae, Psettodidae, and Soleidae).…”
Section: Discussionmentioning
confidence: 99%
“…Fonseca et al (2019) reported juvenile specimens of Serrasentis sagittifer from the intestines of two flatfish species (Paralichthyidae), i.e., Paralichthys isosceles Jordan, 1891 and Paralichthys patagonicus Jordan, 1889. Barton and Smales (2015), Barton et al (2018), and Fonseca et al (2019) mentioned that the flatfish species are paratenic hosts in the life cycle of S. sagittifer. Amin and Heckmann (2021) reported juveniles and adults of S. sagittifer from eight paratenic (from five fish families, one of which belongs to the family Paralichthyidae) and one definitive host species in the Arabian Gulf, and they discussed their world-wide distribution and comparative morphometrics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations